KUMBANG CERAMBYCID (COLEOPTERA) PADA TIPE LAHAN BERBEDA DI KABUPATEN SIAK PROVINSI RIAU, INDONESIA - Ennie Chahyadi; F.Fahri; Rahayu Rahayu; Arini Arini (Bio-Lectura : Jurnal Pendidikan Biologi, 2022)
Siak Regency, Riau Province has a high heterogeneity of vegetation with different types of land. This study aims to determine the types of cerambycid on different types of land in Siak Riau, Indonesia. The method used was Artocarpus trap with collection days consisting of days 4, 7, 10, 13, and 16 after the traps were set up. The collection was carried out on 3 different lands, namely oil palm plantations, rubber and settlements in Buantan Lestari Village, Bungaraya District, Siak Regency, Riau Province. The beetles obtained were then made into an insectarium and identified by looking at the characters on the head, thorax, and abdomen. The results obtained as many as 11 types of cerambycid from 3 subfamilies. The most common types of beetles came from the genus Pterolophia from the Lamiinae subfamily on rubber plantations. Differences in vegetation and habitat conditions affect the number of species and individuals of Cerambycid located on different lands in Siak Regency, Riau Province, Indonesia. Keywords: Land use, longhorns beetle, Cerambycidae, Riau Province, Artocarpus trap